Respostas

2013-04-15T01:04:59-03:00

se eu entendi vc quer um exemplo de equação ne!

 

 

a) 2x - 6 = - x + 15                                       b) 2(x - 3) - 4x = - 3x - 8 

2x + x = 15 + 6                                                 2x - 6 - 4x = - 3x - 8   

3x = 21                                                             2x - 4x + 3x = - 8 + 6

x = 21/3                                                                  x = - 2 

x = 7                                                                      x = - 2

S = {7}                                                                    S = {-2}

 

 

 

 

c) 8x - (x + 3) = 11                                       d) 100x + 80 = 120x - (40x - 300)

  8x - x - 3 = 11                                                 100x + 80 = 120x -40x + 300

  8x - x = 11 + 3                                                   100x - 120x + 40x = 300 - 80

     7x = 14                                                             140x -120x = 220

    x = 14/7                                                                 20x = 220

    x = 14/7                                                                     x = 220/20

 x = 2  → S = [2}                                                               x = 11

                                                                                      S = {11}

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

2 3 2